The international mobility of highly skilled workers in transnational corporations: the macro and macro factors of the organizational migration of cadres - Peixoto, João (2001)
The worldwide movement of highly skilled workers (cadres) in transnational corporations has long been known to literature in the field, yet has not been thoroughly researched. The mechanisms governing their international circulation are, in themselves, somewhat specific. The fact that they use an organizational “channel” for migration means that the constraints differ from those that act on “independent” economic migrants with either low or high levels of skill (the so-called brain drain). This article focuses on some of the manifestations of this mobility. Its dependence on a set of variables can be considerable: the firm’s development phase, investment target choice, leading activity (manufacturing or services), form of technology, type of firm (using greenfield or brownfield investment), whether a firm acquired is healthy or undergoing an economic crisis, and nationality or corporate culture. The occupational insertion of cadres leads to further constraints: while the strictly ‘technical” assignments generally stem from skill shortages, the general “management” appointments mainly result from questions arising from control and trust. As a whole, the flows of highly skilled workers seem to be related to multiple variables - either social, organizational or individual - which make it difficult to predict future trends.